2011
DOI: 10.1177/0269216311397688
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of UK doctors towards euthanasia and physician-assisted suicide: A systematic literature review

Abstract: UK doctors appear to oppose the introduction of AVE and PAS, even when one considers the methodological limitations of included studies. Attempts to minimise bias in included studies varied. Further studies are necessary to establish if subgroup variables other than degree of religiosity influence attitudes, and to thoroughly explore the qualitative themes that appeared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…SCEN physicians are familiar with the legal boundaries, have affinity with EAS, and their experience as consultants might have influenced their standpoint on EAS. In line with previous findings,16 17 we found that religious physicians (93% Christian) were less likely to find it conceivable that they would perform EAS than non-religious physicians. These physicians probably reject EAS on the basis of religious principles, such as the sanctity of life argument 25…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SCEN physicians are familiar with the legal boundaries, have affinity with EAS, and their experience as consultants might have influenced their standpoint on EAS. In line with previous findings,16 17 we found that religious physicians (93% Christian) were less likely to find it conceivable that they would perform EAS than non-religious physicians. These physicians probably reject EAS on the basis of religious principles, such as the sanctity of life argument 25…”
Section: Discussionsupporting
confidence: 92%
“…While 64% were willing to perform EAS in a patient with advanced cancer, only 6–11% were willing to do so in a patient with advanced dementia or in the absence of severe disease 15. As far as we know, there are no other studies on the relationship between cause of suffering and physicians’ willingness to perform EAS 16 17…”
Section: Introductionmentioning
confidence: 99%
“…Most physicians in most countries are against active euthanasia, defined as a measure taken with the definite intention to end life at the patient's explicit request due to refractory suffering (further, we will use the term ‘euthanasia’ to refer to voluntary active euthanasia) 1 2. There is, however, notable variation in the percentage of physicians supporting euthanasia.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is no published study comparing the views of UK veterinarians with those of other UK groups. However, a recent survey of the UK general public ( Sunday Times readers) found that the majority (69 per cent of 1760 respondents) would support the legalisation of assisted suicide in the case of terminal illness (YouGov 2012), while a systematic review of UK doctors’ views indicated that the majority were opposed to assisted dying (McCormack and others 2012). …”
Section: Introductionmentioning
confidence: 99%